2005
DOI: 10.1590/s1677-04202005000400002
|View full text |Cite
|
Sign up to set email alerts
|

Yield and composition of the essential oil of Mentha piperita L. (Lamiaceae) grown with biosolid

Abstract: This research evaluated the effects of biosolid levels on yield and chemical composition of Mentha piperita L. essential oil. Mint plants were grown in a greenhouse in pots containing the equivalent to 0, 28, 56, and 112 t.ha-1 biosolid. Three evaluations were made at 90, 110, and 120 days after planting (DAP). The oil was extracted from the dry matter of shoots by hydrodistillation, and composition was determined by GC/MS. Oil production was slightly affected by the biosolid, increasing when plants were grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
4
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 15 publications
3
39
4
4
Order By: Relevance
“…Similar results were observed by Scora and Chang (1997) in M. piperita L., who did not observe oil yield differences among plants grown with biosolids applications at 100 days after transplanting. Although in the present work, a biosolids effect in essential oil yield was not observed, Scavroni et al (2005) reported that biosolids promoted alterations on M. piperita L. essential oil composition under the same conditions used here. For the essential oil content, which results from secondary metabolism, two considerations can be done.…”
Section: Resultscontrasting
confidence: 52%
“…Similar results were observed by Scora and Chang (1997) in M. piperita L., who did not observe oil yield differences among plants grown with biosolids applications at 100 days after transplanting. Although in the present work, a biosolids effect in essential oil yield was not observed, Scavroni et al (2005) reported that biosolids promoted alterations on M. piperita L. essential oil composition under the same conditions used here. For the essential oil content, which results from secondary metabolism, two considerations can be done.…”
Section: Resultscontrasting
confidence: 52%
“…Veronese et al (2001) reported that biotic and abiotic agents affect essential oil composition in M. piperita. These findings were confirmed in other studies on fertilization effect on the development of this plant (Scavroni et al 2005). Treatment with different levels of nitrogen affects essential oil formation (Piccaglia et al 1993).…”
Section: Discussionsupporting
confidence: 84%
“…The findings of other investigations (Charles et al 1990;Tabatabaie et al 2007) on mint grown in various osmotic stress levels produced similar results. Scavroni et al (2005) showed that biosolid was harmful for formation of menthol. Tounekti et al (2008) studied the effect of increasing concentrations of NaCl on the essential oil composition of Rosmarinus officinalis.…”
Section: Effect Of Nacl and Iron Nanoparticles On Mentha Piperita Essmentioning
confidence: 99%
“…O limoneno é o precursor da carvona e, por reações sucessivas a partir da pulegona, pode formar mentona, mentol, isomentona, neoisomentol e/ou mentofurano. A interconversão dos componentes de um a outro é determinada geneticamente e pode ser afetada por fatores agronômicos (MAIA et al, 2001;TELCI et al, 2004;SCAVRONI et al, 2005). Com base nisso, as condições de variação nas concentrações de K nas soluções hidropônicas às quais as plantas de M. x gracilis foram submetidas favoreceram a formação dos compostos linalol, carvona e cis-hidrato de sabineno.…”
Section: Resultsunclassified